2009
DOI: 10.1139/b09-040
|View full text |Cite
|
Sign up to set email alerts
|

Aegilops sharonensis:Origin, genetics, diversity, and potential for wheat improvement

Abstract: Aegilops sharonensis  Eig (Sharon goatgrass; section Sitopsis) is an annual diploid grass species growing endemically in the coastal plains of Israel and southern Lebanon. It is a wild relative of wheat, with a genome closely related to the B genome of cultivated bread wheat. With the most limited distribution of any species in the genus Aegilops, Ae. sharonensis is rapidly losing its habitats, owing to the combined effects of modern agricultural intensification and expansion of urban and industrial areas. Aeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 116 publications
0
22
0
Order By: Relevance
“…As the magnitude of diversity and availability of plant resources are vital for crop improvement (Govindaraj et al, 2015), estimation of genetic diversity and relationships between crop germplasms is the key step (Rafalski, 2011) and the loss of genetic diversity is : Not significant a major danger for the survival and breeding of crop species (Olivera and Steffenson, 2009). Phenotypic data have been used to compare individual genotypes and populations of crop species with the aim of optimizing characterization, determining characters variations, associations and establishing genetic relationship within species.…”
Section: Discussionmentioning
confidence: 99%
“…As the magnitude of diversity and availability of plant resources are vital for crop improvement (Govindaraj et al, 2015), estimation of genetic diversity and relationships between crop germplasms is the key step (Rafalski, 2011) and the loss of genetic diversity is : Not significant a major danger for the survival and breeding of crop species (Olivera and Steffenson, 2009). Phenotypic data have been used to compare individual genotypes and populations of crop species with the aim of optimizing characterization, determining characters variations, associations and establishing genetic relationship within species.…”
Section: Discussionmentioning
confidence: 99%
“…Exceptional is Aegilops speltoides that provided 6 leaf rust resistance genes Lr28, 35, 36 47 51 and 66 [9]. Aegilops sharonensis Eig (Sharon goatgrass) was found to possess resistance against different wheat diseases including leaf, stripe and stem rusts, powdery mildew, tan spot and spot blotch [12] but has not been widely exploited [13]. In 2006, Marais et al reported on transferring resistance to leaf rust (Lr56) and stripe rust (Yr38) to chromosome 6A of wheat, while recently, Millet et al [14] reported on introgressing resistance to the devastating stem rust race TTKSK (Ug99) from Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Introgressing resistance genes from Ae. sharonensis into wheat is not trivial because it involves special cytogenetic techniques and dealing with gametocidal genes that control the preferential transmission of certain chromosomes (Olivera and Steffenson 2009). Additionally, as with all exotic sources of resistance, linkage drag can be a problem.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as with all exotic sources of resistance, linkage drag can be a problem. Still, a number of researchers have successfully transferred genes from this species into wheat (Olivera and Steffenson 2009). Marais et al (2006) reported the introgression of a leaf rust and stripe rust resistance gene from Ae.…”
Section: Discussionmentioning
confidence: 99%